THE EFFECT OF JOB PERFORMANCE THROUGH ORGANIZATIONAL CULTURE, WORK ENVIRONMENT, PERSONALITY, AND MOTIVATION - Virgana Virgana (Jurnal Manajemen dan Kewirausahaan, 2020)
The dominant factor to achieve a school's competitiveness is the performance of headmasters. This study aimed to determine the direct and indirect influence of organizational culture, work environment, personality, and motivation on the performance of principal of state senior high schools.  Research samples were 310 principals of state schools in Jakarta. Data analysis used a path analysis of which requirements were the test of normality, homogeneity, and linearity. The results of the research there were direct influence exogenous variables on endogenous, and there was indirect influence of personality through motivation on the job performance. Increased job performance could be done by coaching the headmaster about the culture, environment, and personality